The relationship of cortical folding and brain arteriovenous malformations. Issue 1 (December 2016) - Shah, Manish; Smith, Sarah; Dierker, Donna; Herbert, Joseph; Coalson, Timothy; Bruck, Brent; Zipfel, Gregory; Van Essen, David; Dacey, Ralph
Abstract Background The pathogenesis of human intracranial arteriovenous malformations (AVMs) is not well understood; this study aims to quantitatively assess cortical folding in patients with these lesions. Methods Seven adult participants, 4 male and 3 female, with unruptured, surgically unresectable intracranial AVMs were prospectively enrolled in the study, with a mean age of 42.1 years and Spetzler-Martin grade range of II-IV. High-resolution brain MRI T1 and T2 sequences were obtained. After standard preprocessing, segmentation and registration techniques, three measures of cortical folding, the depth difference index (DDI), coordinate distance index (CDI) and gyrification index (GI)), were calculated for the affected and unaffected hemispheres of each subject as well as a healthy control subject set. Results Of the three metrics, CDI, DDI and GI, used for cortical folding assessment, none demonstrated significant differences between the participants and previously studied healthy adults. There was a significant negative correlation between the DDI ratio between affected and unaffected hemispheres and AVM volume (correlation coefficientr  = -0.74, p  = 0.04). Conclusion This study is the first to quantitatively assess human brain cortical folding in the presence of intracranial AVMs and no significant differences between AVM-affected versus unaffected hemispheres were found in a small dataset. We suggest longitudinal, larger human MRI-based cortical folding studies to assess whether AVMs are congenital lesions of vascular development orde novo, dynamic lesions.